Methodology of Multimedia Technologies in English Lessons of Technical Education - Baxadirovna, Mahamadalieva Nilufar; Ibragimjanovna, Isomiddinova Lola; Toxirovna, Pardaeva Diyora (International Journal of Psychosocial Rehabilitation, 2020)
Multimedia (multiple media, eng.) is the interaction of visual and audio information under the control of interactive software using modern hardware and software, they combine text, sound, graphics, photos, videos in one digital representation. For example, a single container object can contain text, audio, graphics, and video information, and possibly a way to interact with it. The term multimedia is also often used to refer to media that can store large amounts of data and provide fairly quick access to them (the first media of this type were CD — compact disk). In this case, the term multimedia means that the computer can use such media and provide information to the user through all possible types of data, such as audio, video, animation, image and others in addition to traditional ways of providing information, such as text. The definition given above is actually a user definition, that is, a General simplified definition of multimedia for the understanding of the computer user. The scientific and technical definition of multimedia is somewhat different.